Pengembangan Media Pembelajaran Berbasis Cerita Bergambar Untuk Meningkatkan Hasil Belajar Siswa Kelas V SDIT Persada Bayat - Khasana Kurniawati; Tukiyo Tukiyo; Bayu Purbha Sakti (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The background to this research is the minimal use of learning media, which makes learning tend to be monotonous, resulting in low student learning outcomes, especially in science and science subjects, material on economic activity processes. The aim of this research is to develop picture story-based learning media to improve the learning outcomes of class V students at SDIT Persada Bayat. This type of research is research and development (R&D) with the ADDIE model, which has stages of analysis, design, development, implementation and evaluation. The analysis techniques used are descriptive statistics, t-test and N-gain. Based on the results of material and language expert validation, the average percentage was 84.09% (very feasible), media expert validation was 91.67% (very feasible), and practitioner expert validation was 75% (decent). The practicality of the media from the student response questionnaire received an average percentage of 93.75% (very practical). Student learning achievement test scores experienced a significant increase with an average N-gain score percentage of 66.89% (quite effective). The results of this development research show that picture story-based learning media is feasible, practical and quite effective.